Biochemical and Physiological Evaluations of Limonoids As Potential Cancer Destroyers - Bayazit, V.; Konar V. (My University, 2010)
The aim of this study was evaluated the anticancerogen properties of limonoids and their biochemical structures. The term limonoids was derived from limoinn, the first tetranortriterpenoid obtained from citrus bitter principles. Compounds belonging to this group have exhibited a range of biological activities like insecticidal, insect antifeedant and growth regulating activity on insects as well as antibacterial, antifungal, antimalarial, anticancer, antiviral and a number of other pharmacological activities on humans. Limonoids found in citrus fruits have been able to stop the progression of neuroblastomas in the laboratory. It also produces no side effects unlike the currently used toxic cancer drugs. Further research is needed to determine how the substance achieves this effect and how it may be used in human cancers. Both flavenoids and limonoids may be capable of stopping, slowing or killing cancer cells. Ultimately, these compounds could be used as food additives as a preventative measure. The effects of D-limonene and citrus, orange oil and lemon oil on induced neoplasia of the lungs and forestomach of female mice inhibited pulmonary adenoma formation and the occurrence of forestomach tumors, thus demonstrating that non-nutrient constituents of the diet may inhibit carcinogen-induced neoplasia. © Medwell Journals, 2010.
Keywords: Anti material; Biochemical structures; Biological activities; Cancer; Limonoids; Turkey